2012
DOI: 10.1007/s10570-012-9728-y
|View full text |Cite
|
Sign up to set email alerts
|

AKD-Modification of bacterial cellulose aerogels in supercritical CO2

Abstract: Different approaches towards hydrophobic modification of bacterial cellulose aerogels with the alkyl ketene dimer (AKD) reagent are presented. If AKD modification was performed in supercritical CO 2 , an unexpectedly high degree of loading was observed. About 15 % of the AKD was bound covalently to the cellulose matrix, while the other part consisted of re-extractable AKD-carbonate oligomers, which are novel chemical structures described for the first time. These oligomers contain up to six AKD and CO 2 moieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Typically, the procedures reported involved cellulose dissolved in a lithium chloride/1, 3-dimethyl-2-imidazolidinone (LiCl/DMI) system, where subsequently reaction with AKD melt under homogeneous condition took place. Cellulose fibers were modified heterogeneously by AKD vapor redeposition (Hutton and Shen 2005;Zhang et al 2007) or impregnated with subcritical and supercritical carbon dioxide (Hutton and Parker 2009;Russler et al 2012). However, these treatment processes are always laborious or result in uneven AKD distribution, which may limit their suitability for scaling up in industry.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the procedures reported involved cellulose dissolved in a lithium chloride/1, 3-dimethyl-2-imidazolidinone (LiCl/DMI) system, where subsequently reaction with AKD melt under homogeneous condition took place. Cellulose fibers were modified heterogeneously by AKD vapor redeposition (Hutton and Shen 2005;Zhang et al 2007) or impregnated with subcritical and supercritical carbon dioxide (Hutton and Parker 2009;Russler et al 2012). However, these treatment processes are always laborious or result in uneven AKD distribution, which may limit their suitability for scaling up in industry.…”
Section: Introductionmentioning
confidence: 99%
“…Lightweight aerogels (8.25±0.7 mg.cm -3 ) with well-defined porous structure (10 nm) and high surface area (200 m 2 /g) were obtained. Hydrophobization of aerogels prepared from bacterial cellulose was achieved by reaction with alkyl ketene dimer through different methodologies followed by supercritical drying in CO 2 (Russler et al, 2012).…”
Section: Structuring Of Nanocellulose At Liquid-liquid Interfaces: Emmentioning
confidence: 99%
“…Evacuation of solvents in supercritical conditions is commonly used to produce aerogels which is a term given to open pore materials presenting low density and large specific surface area. The most known aerogels are silica, (Murillo-Cremaes et al 2010;Moner-Girona et al 2003;Martin et al 2008;Budunoglu et al 2011) carbon, (Wu et al 2013;Mecklenburg et al 2012) organic-inorganic aerogels (Hendel et al 2013;Ennajih et al 2012) and more recently thick pieces of BC aerogels have also been reported (Hendel et al 2013;Liebner et al 2010;Cai et al 2008;Russler et al 2012).…”
Section: Introductionmentioning
confidence: 99%